Design Interference Detector-A Tool for Predicting Intrinsic Design Failures - D’Amelio, V.; Tomiyama, Tetsuo (Cranfield University Press, 2009)
Intricate failures at the system integration phase of the design are mostly generated by interactions of product modules or/and engineering domains. Modules of the product are tested independently and when their integration is performed, design failures are detected. This significantly delays the machine development. This paper aims at introducing a software tool able to predict phenomena which generate destructive couplings of engineering domains and product modules. An example shows how these couplings influence the system behaviors. The analysis is conducted at the conceptual deign level and makes use of qualitative data to reason out behaviors of the product.
Organised by: Cranfield University
Keywords: Mechatronics; Unpredicted problems; Qualitative Physics; Verification; Integration